Public Preferences for Government Spending Priorities: Survey Evidence from Germany - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
Employing data from a representative survey conducted in Germany, this paper examines public preferences for the size and composition of government expenditure. We focus on public attitudes toward taxes, public debt incurrence, and public spending in six different policy areas. Our findings suggest, first, that the current scope of government is supported by a majority of the German population. Second, we find that individual preferences for the composition of government spending differ along various dimensions. Specifically, personal economic well-being, economic literacy, confidence in politicians, political ideology, and time preference are significantly related to individual attitudes toward public spending, taxes, and debt. The magnitude of the effects is particularly large for time preference, economic knowledge, and party preference. Third, public preferences for public spending priorities are only marginally affected when considering a public budget constraint.
Keywords: E62; H11; H50; H63; 330; Public spending; public preferences; public debt; taxes; survey; Germany.